Size estimations of sturgeons (Acipenseridae) from the Mesolithic-Neolithic Danube Gorges - Ivana Živaljević; Igor V. Askeyev; Dilyara N. Shaymuratova (Galimova); Oleg V. Askeyev; Sergey P. Monakhov; Dušan Borić; Sofija Stefanović (Serbian Archaeological Society & Italian Academy for Advanced studies ‒ Columbia University, 2020)
The significant role of sturgeon fishing in the Mesolithic-Neolithic Danube Gorges has long been recognized, but the reconstruction of the sizes of individuals caught has been hindered by the lack of recent specimens from the Danube drainage in reference collections. This paper presents a method to reconstruct the total length from skeletal remains of several sturgeon species ( Huso huso , Acipenser gueldenstaedtii , A. nudiventris , A. stellatus , and A. ruthenus ) using linear and power regression equations, obtained from the database of biometric data of recent sturgeons from the Volga-Caspian Basin. The application of these regression equations to specimens from the Danube Gorge sites of Lepenski Vir, Padina, and Vlasac suggests that sturgeon fishing was oriented towards large adult individuals, with the largest specimens (in the case of beluga) surpassing550 cm in total length. In addition to providing means for predicting body size of sturgeon specimens from archaeological contexts in areas where modern sturgeon stocks are diminished or completely extirpated, this study has important implications for investigating nutritional values, fishing techniques, and human-animal interrelationships in the Mesolithic-Neolithic Danube Gorges.